TINJAUAN TERKAIT DENDA PADA RESTORAN DENGAN KONSEP ALL YOU CAN EAT DALAM PERSPEKTIF SYARIAH (STUDI KASUS RESTORAN KINTAN BUFFET KOTA KASABLANKA) - Mughni, Abdul; Hanifah Latief, Amalia (INSTITUT AGAMA ISLAM TAZKIA, 2021)
This thesis aims to find out how the law for the inclusion of a fine clause in the all-you-can-eat restaurant at the Kintan Buffet Kota Kasablanka restaurant is in accordance with the sharia perspective. Data collection was carried out by observation and conducting interviews and documentation during the research. The results of this study are that there are two views from the scholars of madzhab regarding the law of the fine clause (syarth jaza'i), namely the opinion that it is not permissible if the inclusion of the fine clause is related to debts and receivables, because the fine in this case is the same as usury so it is forbidden, but if other than that which is not related to debts, fines in this case are allowed and this is a rojih opinion. The second opinion is that it is not allowed to include a fine clause at all. The practice of applying clauses/provisions of fines at the all-you-can-eat restaurant Kintan Buffet Kota Kasablanka as a whole from the results of the study shows that it does not conflict with sharia principles and is not a fine clause (syarth jaza'i) related to debts and receivables.